2007
DOI: 10.1007/s12111-007-9016-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Prostate Cancer Screenings among African American Men: Combining the Behavioral Science and Anthropological Perspectives

Abstract: This paper synthesizes the perspectives from behavioral science and medical anthropology to discuss factors affecting prostate cancer screenings among African American men. It argues that the hegemonic health behavior model historically used to frame prostate cancer screenings without considering the context in which African American men are embedded. By the same token, the sociocultural perspective tends to articulate the cultural meaning and social relationships experienced by patients; however, it may opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The literature on gender as a barrier to screening also took a critical approach to the combination of social norms and mores which limit men's and women's engagement with certain kinds of screening, in a similar vein to the literature on biography and risk perceptions discussed previously. For example, Lu () explores dominant depictions of masculinity and intimate relationships among African American men, and others consider the conventions of modesty or embarrassment as expressed by Vietnamese, Muslim and Malay women undergoing intimate examinations in the US (Dunn and Tan , Faik Salman , Nguyen and Clark ).…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 99%
“…The literature on gender as a barrier to screening also took a critical approach to the combination of social norms and mores which limit men's and women's engagement with certain kinds of screening, in a similar vein to the literature on biography and risk perceptions discussed previously. For example, Lu () explores dominant depictions of masculinity and intimate relationships among African American men, and others consider the conventions of modesty or embarrassment as expressed by Vietnamese, Muslim and Malay women undergoing intimate examinations in the US (Dunn and Tan , Faik Salman , Nguyen and Clark ).…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 99%
“…Previous research studies on prostate cancer have shown that removal of behavior‐related barriers would increase the likelihood of African American men engaging in prostate cancer screening and treatment programs (Robinson, Ashley, & Haynes, ; Smith, Catalona, & Herschman, ). Although there is clearly a need for prevention and education techniques to aid in decreasing the number of African American men developing prostate cancer (Lu, ), health professionals suggest that there is no definitive approach; researchers are still striving to establish which prostate cancer prevention strategy is most effective and safe (Mayo Clinic Staff, ).…”
Section: Prostate Cancer and African American Malesmentioning
confidence: 99%